The Influence of Job Insecurity and Job Satisfaction on Turnover Intention of Millenial Employees in the Industrial Revolution 4.0 - Donifan Alfianda; Christantius Dwiatmadja (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is motivated by the condition of the industrial revolution 4.0 and human resources that are decreasing even more desire to leave (turnover intention) in employees, especially in the millennial generation. Where the loyalty level of millennials is still relatively low, so millennial employees easily have plans to leave the company where they work. The purpose of this study was to find out whether job insecurity and job satisfaction partially affect the turnover of millennial employees' intentions in the industrial revolution 4.0. The data collection method is done through a questionnaire in the form of google form which was distributed to millennial employees of UKSW. The samples taken were 97 people. Statistical analysis used in this research is validity and reliability test, classical assumption test, regression analysis, hypothesis testing and coefficient of determination analysis. The data obtained were then processed with SPSS and analyzed using multiple linear regression analysis. The results of the analysis show that job insecurity and job satisfaction have a positive and significant impact on the turnover intention of millennial employees in the industrial revolution 4.0 era.